APAKAH BENAR PERILAKU CYBERLOAFING AKIBAT BEBAN KERJA DAN STRES KERJA YANG BERLEBIHAN? - Pangestuari, Ikhsan; Karyatun, Subur; Permana Sultoni, Rillo; Saratian, Eko Tama Putra; Soelton , Mochamad; Nurul Hidayat, Tegar (Jurnal Keuangan dan Bisnis, 2023)
In order to ascertain the effect of Burnout-mediated cyberloafing behavior on employee performance, this study will examine workload and work stress. The five divisions of the Ministry of Youth and Sports of the Republic of Indonesia that were permitted to serve as research samples made up the study's population. There were sixty employees in the sample. Purposive sampling, or the practice of acquiring samples that meet specific requirements, is the sampling approach employed in this study. A questionnaire serves as the study instrument in this survey-based data collection method. techniques for partial least squares data processing. This study demonstrates that cyberloafing behavior is significantly influenced by workload behavior. The practice of cyberloafing is not significantly impacted by job stress. Burnout is significantly impacted by workload. Burnout is significantly impacted by work stress. Cyberloafing is significantly impacted by Burnout. Both directly and indirectly, through Burnout as a mediating variable, workload affects cyberloafing. Burnout acts as a mediator variable between work stress and cyberloafing.